Transparent electrode and measuring instrument

A laminated transparent electrode with SnO2 and a current collector enhances durability, allowing both electrical and optical measurements to be integrated on wearable devices, improving design flexibility and accuracy.

JP2024178538APending Publication Date: 2024-12-25SAMSUNG ELECTRONICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023096739
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Conventional transparent electrodes used in wearable devices lack durability and design flexibility due to their placement inside closed spaces, limiting the integration of both electrical and optical measurement sections, which are typically opaque and transparent, respectively.

Method used

A transparent electrode with a laminated structure comprising an insulating substrate, a conductive layer, and a transparent electrode layer made of SnO2, optionally with added elements, and a current collector for enhanced durability and conductivity, allowing placement on the outermost surface of devices.

Benefits of technology

The transparent electrode provides physical and chemical durability, enabling both electrical and optical measurement sections to be integrated on the same surface, improving design freedom and accuracy of biological information acquisition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178538000001_ABST
    Figure 2024178538000001_ABST
Patent Text Reader

Abstract

To provide a transparent electrode having durability of withstanding arrangement on an outermost surface of a device and improving flexibility in design of the device by combinedly using an electric measuring part and an optical measuring part.SOLUTION: A transparent electrode 1 formed on an insulating substrate 10 and coming into contact with an object such as a human body to be electrically connected thereto, the transparent electrode 1 has a laminated structure formed by laminating a transparent electrode layer 20 consisting primarily of SnO2, and a conductive layer 30 formed of a metallic layer 31 and / or a metal-oxide layer 32 with conductivity, in this order from an outermost side, where at least a part of a lateral face 21 of the transparent electrode layer 20 is covered with a power collecting part 40 electrically connected to the transparent electrode layer 20 and the conductive layer 30.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent electrode that can be mounted on a measuring instrument such as a wearable device, and to a measuring instrument equipped with the electrode. [Background technology]

[0002] Patent document 1 discloses a display unit in which a display cell is arranged within a case having a back cover, the display cell comprising a transparent front substrate having a first transparent electrode on its inner surface, a transparent rear substrate having a second transparent electrode on its inner surface, and a fixing frame for the two substrates that forms a closed space between the substrates, and the display cell is caused to display temporal information by a control means. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-121303 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, with the rise in health consciousness, the demand and applications of smart wearable devices that can monitor the physical health condition in real time are expanding rapidly.

[0005] There are two general methods for acquiring biometric information in wearable devices: electrical measurement and optical measurement. When performing optical measurement, the exterior components of the optical measurement unit must have high transmittance at the wavelength used in the measurement. On the other hand, when performing electrical measurement, the electrical measurement unit is generally composed of metal electrodes and is optically opaque. Therefore, in the limited exterior area of ​​a wearable device, it is difficult to arrange both electrical and optical measurement units on top of each other, especially when both units are installed, and the degree of freedom in design is low.

[0006] When the above-mentioned two types of measuring units are mounted on a wearable device, it is possible to use a well-known transparent electrode. Usually, the transparent electrode is formed of a material such as ITO having both high electrical conductivity and optical transparency, as in the conventional transparent electrodes including those in Patent Document 1. However, this type of transparent electrode is typically used by being placed in an enclosed space such as inside a case, and durability is not taken into consideration. Therefore, it is not possible to place it on the outermost surface of the device, and the degree of freedom of design cannot be improved.

[0007] The present inventors have conducted extensive research to solve the problems associated with conventional transparent electrodes, and have succeeded in developing a novel transparent electrode that combines physical and chemical durability while maintaining transparency, something that was not considered in conventional transparent electrodes, thereby arriving at the present invention.

[0008] The present invention has been made in consideration of the above-mentioned circumstances, and specifically, an object of the present invention is to provide a transparent electrode and measuring instrument that have physical and chemical durability sufficient to withstand placement on the outermost surface of a device while ensuring transparency, and that can improve the design freedom of the device by using an electrical measuring unit and an optical measuring unit in combination. [Means for solving the problem]

[0009] The above object of the present invention can be achieved by any one of the following (1) to (7).

[0010] (1) A transparent electrode formed on an insulating substrate and electrically connected to an object by contacting the object, the transparent electrode being made of SnO 2 and a conductive layer formed of a metal layer and / or a metal oxide layer having electrical conductivity, the metal layer having an opening formed so that a portion of the transparent electrode layer can come into contact with the insulating substrate, the conductive layer being laminated in this order from the outermost surface side, and at least a portion of a side surface of the transparent electrode layer is covered with a current collecting portion electrically connected to the transparent electrode layer and the conductive layer.

[0011] (2) The transparent electrode described in (1) above, wherein the metal layer of the conductive layer is formed so that, when the thickness of the metal layer exceeds 5 nm, its projected area on the insulating substrate in a planar view is 30% or less of the area of ​​the insulating substrate.

[0012] (3) The transparent electrode according to (1) or (2) above, wherein the metal layer contains one or more elements selected from Ag, Al, Cr, Cu, Au, Pt, Ti, Mo, Nb, and Nd, and the transparent electrode layer contains one or more elements selected from In, Ga, Nb, Ta, W, Zn, Sn, Zr, Si, and F.

[0013] (4) A transparent electrode described in any of (1) to (3) above, wherein the metal layer has a first metal portion formed of a first metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd, and a second metal portion formed of a second metal selected from the group consisting of Ag, Al, Cr, Cu, and Nb, and the first metal portion is positioned so as to prevent exposure of the second metal portion.

[0014] (5) The transparent electrode according to any one of (1) to (4) above, wherein the current collecting portion is formed of a first metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd, and is formed so as to cover at least a portion of the side portion of the transparent electrode layer and the outermost surface of the conductive layer.

[0015] (6) The transparent electrode according to any one of the above (1) to (5), wherein the transparent electrode layer has a film thickness of 50 nm or more and 200 nm or less.

[0016] (7) A measuring instrument comprising the transparent electrode according to any one of (1) to (6) above. Effect of the Invention

[0017] The transparent electrode of the present invention has physical and chemical durability that can withstand being placed on the outermost surface of a device while ensuring transparency, and can be used as an electrode of an electrical measurement section by placing a transparent electrode layer on the outermost surface. Therefore, since the electrode part, which was conventionally optically opaque, can be made transparent, it is possible to place an electrical measurement section and an optical measurement section in a layered manner in a wearable device with a relatively small exterior area. Therefore, a wearable device equipped with the transparent electrode of the present invention has a higher degree of freedom in the measurement method while reducing design constraints, and more optical measurements are possible. In addition, by using the transparent electrode of the present invention, optical acquisition of biological information over a larger area is possible, and the measurement accuracy of biological information can be improved. Furthermore, when the electrode part is composed of only a metal electrode, the exterior is limited to a metallic opaque material from the viewpoint of design, but by using the transparent electrode of the present invention, it is possible to apply a design to the lower layer of the electrode, and the design of the device can also be improved. [Brief description of the drawings]

[0018] [Figure 1] 1 is a conceptual diagram of a wearable device which is a measuring instrument according to a preferred embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a transparent electrode according to the present embodiment. [Diagram 3] FIG. [Figure 4] 13A and 13B are diagrams showing modified examples of the conductive layer of the transparent electrode. [Diagram 5] FIG. 11 is a cross-sectional view of a transparent electrode according to Modification 1. [Figure 6] FIG. 11 is a cross-sectional view of a transparent electrode according to Modification 2. [Figure 7] FIG. 11 is a cross-sectional view of a transparent electrode according to Modification 3. [Figure 8] FIG. 13 is a cross-sectional view of a transparent electrode according to Modification 4. [Figure 9] 1 is a table showing the evaluation results of Examples 1 to 3 in Evaluation Test 1 of the Examples. [Figure 10] 1 is a table showing the evaluation results of Examples 4 to 6 in Evaluation Test 1 of the Examples. [Figure 11]1 is a table showing the evaluation results of Comparative Examples 1 to 4 in Evaluation Test 1 of the Examples. [Figure 12] 1 is a table showing the evaluation results of Example A, Example B, and Comparative Example C in Evaluation Test 2 of the Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, the embodiments for carrying out the present invention will be described in detail with reference to the drawings. The embodiments shown here are merely illustrative in order to embody the technical idea of ​​the present invention, and do not limit the present invention. Furthermore, all other embodiments, examples, and operational techniques that can be conceived by those skilled in the art without departing from the gist of the present invention are included in the scope and gist of the present invention, and are included in the scope of the inventions described in the claims and their equivalents.

[0020] Furthermore, for the convenience of illustration and ease of understanding, the drawings attached to this specification may be represented diagrammatically with appropriate changes in scale, aspect ratio, shape, etc. from the actual product; however, these are merely examples and are not intended to limit the interpretation of the present invention.

[0021] Unless otherwise specified, the operation and physical properties are measured at room temperature (20°C or higher and 25°C or lower) and a relative humidity of 40% RH or higher and 50% RH or lower.

[0022] In the following description, when ordinal numbers such as "first" and "second" are used, unless otherwise specified, they are used for convenience and do not dictate any order.

[0023] In the following embodiment, a wristwatch-type wearable device is exemplified as a measuring device equipped with the transparent electrode 1 according to the present embodiment. However, the measuring device equipped with the transparent electrode 1 of the present invention can be applied to other wearable devices other than wristwatch-type devices and other devices other than wearable devices, so long as the measuring device measures information of a subject, such as biological information.

[0024] The configuration of a transparent electrode 1 according to one embodiment of the present invention will be described with appropriate reference to Fig. 1 to Fig. 8. However, Fig. 1 to Fig. 8 relate to a transparent electrode 1 and a measuring device according to one embodiment of the present invention, and the transparent electrode 1 of this embodiment is not limited to the configuration described by these figures.

[0025] FIG. 1 conceptually illustrates a part of a wearable device 100, which is a measuring instrument that includes a transparent electrode 1 according to this embodiment and measures predetermined information such as biological information.

[0026] <Wearable devices> Wearable device 100 is a device that is worn on a predetermined part of the wearer's body, such as the arm, when used. Wearable device 100 has a function capable of measuring target information, such as biological information, and, for example, in the case of a wristwatch type, can function as a wristwatch as well as a measuring device.

[0027] 1, the wearable device 100 includes, in a device body 110, an optical measurement unit 120 having a light-emitting unit for emitting light and a light-receiving unit for detecting the intensity of infrared light reflected from inside the living body and for optically measuring biological information such as heart rate and blood flow, an electrical measurement unit 130 for electrically measuring biological information such as body composition (body fat percentage, muscle mass, etc.) by measuring a bioelectric potential, a display unit 140 disposed on the upper surface side of the device body 110 for displaying various information, a control unit 150 for overall control of the drive of each unit, and a power supply unit 160 for supplying drive power to each unit. Note that the configuration of the wearable device 100 is not limited to the above-mentioned configuration, and may include a function realization unit for realizing other functions required as a device configuration.

[0028] <Transparent electrode> 1, the transparent electrode 1 is provided at a predetermined location (for example, on the underside of the device, which is the surface on which the device is worn) of the wearable device 100. The transparent electrode 1 can be disposed at a location that can come into contact with the skin of the wearer.

[0029] As shown in Fig. 2, the transparent electrode 1 includes an insulating substrate 10, a transparent electrode layer 20, a conductive layer 30, and a current collecting portion 40. As shown in Figs. 2 and 3, the transparent electrode 1 has the conductive layer 30 disposed on the insulating substrate 10, the transparent electrode layer 20 disposed on the conductive layer 30, and the current collecting portion 40 disposed so as to cover at least a portion of the side surface portion 21 of the transparent electrode layer 20.

[0030] Insulating Substrate The insulating substrate 10 is made of an insulating material such as non-alkali glass, etc. The insulating substrate 10 cuts off electrical connection between the transparent electrode 1 and the internal equipment of the wearable device 100.

[0031] <Transparent electrode layer> The transparent electrode layer 20 is made of a metal oxide having electrical conductivity, and is disposed on the conductive layer 30. The transparent electrode layer 20 is electrically connected to the conductive layer 30. As shown in Fig. 1, the transparent electrode layer 20 is located on the outermost surface on the lower side of the wearable device 100. Therefore, the transparent electrode 1 can come into contact with and be electrically connected to a subject (such as the skin of a wearer).

[0032] The transparent electrode layer 20 is made of a material that is conductive, transparent, and has physical and chemical durability. The transparent electrode layer 20 is made of SnO 2 It can be composed of metal oxides mainly composed of SnO 2 is an In like ITO. 2 O 3 It is chemically stable and has excellent durability compared to metal oxides that are primarily composed of

[0033] The transparent electrode layer 20 is made of SnO 2 It is preferable to further add one or more elements selected from the group consisting of In, Ga, Nb, Ta, W, Zn, Sn, Zr, Si and F, and it is particularly preferable to add F.

[0034] Suppose the transparent electrode layer 20 is made of SnO 2When the transparent electrode layer 20 according to the present embodiment is formed only from SnO, durability can be obtained, but the surface resistance becomes high, and increasing the film thickness in order to reduce the surface resistance is undesirable because the transparency is impaired. 2 By adding one or more of the above-mentioned elements to the transparent electrode layer 20, when the transparent electrode layer 20 is formed by a sputtering method, the average particle size in the film can be controlled to be small while the surface roughness Ra can be reduced. Furthermore, by reducing the surface roughness Ra of the transparent electrode layer 20, the surface smoothness is improved. Therefore, the transparent electrode layer 20 is less likely to wear when friction occurs between the transparent electrode layer 20 and the skin of the wearer, and can exhibit excellent durability.

[0035] From the viewpoint of durability and transparency, the transparent electrode layer 20 preferably has a thickness of 50 nm or more and 200 nm or less, more preferably more than 60 nm and less than 200 nm. By controlling the thickness of the transparent electrode layer 20 within the above-mentioned range, the durability, conductivity, and transparency of the transparent electrode layer 20 can be ensured. Here, if the thickness of the transparent electrode layer 20 is less than 50 nm, the durability and conductivity may decrease, and the function as the transparent electrode 1 may decrease, which is not preferable. In addition, if the thickness of the transparent electrode layer 20 exceeds 200 nm, the transparency may decrease, and the measurement performance of the optical measurement unit 120 may not be fully exhibited, which is not preferable.

[0036] From the viewpoint of durability, the transparent electrode layer 20 has a surface roughness Ra of 3.3 nm or less, a maximum height roughness Rz of 33 nm or less, and a film density of 6.8 g / cm -3 It is preferable that the surface roughness Ra and the maximum height roughness Rz are equal to or more than the above. The surface roughness Ra and the maximum height roughness Rz can be measured in accordance with JIS B0601-2001. The film density can be measured, for example, by X-ray reflectometry (XRR). By setting the surface roughness Ra, the maximum height roughness Rz, and the film density of the transparent electrode layer 20 to the above values, wear due to friction with the wearer's skin, etc. can be suppressed and high durability can be maintained.

[0037] From the viewpoint of transparency, the transparent electrode layer 20 preferably has an average transmittance of 80% or more for light in the wavelength region of 500 nm or more and 950 nm or less. The average transmittance can be measured in accordance with JIS R3106-2019. By making the transparent electrode layer 20 have an average transmittance of 80% or more, the optical measurement unit 120 can accurately obtain the necessary optical information. If the average transmittance of the transparent electrode layer 20 is less than 80%, the amount of optical information transmitted through the transparent electrode layer 20 decreases, making it difficult for the optical measurement unit 120 to obtain accurate information, which is not preferable.

[0038] From the viewpoint of electrical conductivity, it is preferable that the transparent electrode layer 20 has a resistance between the center and the outer peripheral edge in a planar view of 200 Ω·cm or less, and a surface resistance of the center of 220 Ω / sq or less. As a result, the transparent electrode layer 20 has a higher surface resistance and resistance than a general metal electrode, but has sufficient electrode performance for measuring bioinformation, making it possible to replace conventional metal electrodes. In addition, in order to obtain accurate electrical bioinformation, it is preferable that the resistance of the transparent electrode itself is low.

[0039] Conductive Layer 2, the conductive layer 30 is electrically connected to the transparent electrode layer 20 and the current collecting section 40, and is interposed between the insulating substrate 10 and the transparent electrode layer 20. The conductive layer 30 is connected to an electrical measuring section 130 and the like. The conductive layer 30 is formed of a metal layer 31 and / or a metal oxide layer 32 having electrical conductivity.

[0040] When the conductive layer 30 is formed of only the metal layer 31 or a laminated structure of the metal layer 31 and the metal oxide layer 32, from the viewpoint of transparency, if the film thickness exceeds 5 nm, it is preferable that the projected area on the insulating substrate 10 in a plan view is 30% or less of the area of ​​the insulating substrate 10. Suitable examples of the structure of the conductive layer 30 having such a projected area include a form in which an opening 33 communicating with the insulating substrate 10 is formed, such as (a) a lattice shape, (b) a linear shape, (c) a ring shape, (d) a hollowed-out shape in which a part of the film is hollowed out, and (e) a spiral shape, as shown in Fig. 4.

[0041] The shape, formation position, and opening shape and size of the conductive layer 30, etc., of the opening 33 are not limited to the shape shown in FIG. 4, and can be appropriately designed according to the device configuration (the configuration and position of the optical measurement unit 120 to be mounted, etc.) as long as the projected area onto the insulating substrate 10 is at least 30% or less of the area of ​​the insulating substrate 10.

[0042] The metal constituting the metal layer 31 can be composed of one or more elements selected from Ag, Al, Cr, Cu, Au, Pt, Ti, Mo, Nb, and Nd. Among these metals, a metal selected from the group of Au, Pt, Ti, Mo, and Nd can be classified as a "first metal", and a metal selected from the group of Ag, Al, Cr, Cu, and Nb can be classified as a "second metal". Here, the "first metal" is a highly durable metal that has ease of processing and good durability, but has a property of being somewhat poor in electrical conductivity. The "second metal" is a highly conductive metal that has ease of processing and good electrical conductivity, but has a property of being poor in durability (especially acid and alkali resistance). The conductive layer 30 can be composed of a first metal portion 31A that is a portion formed of the first metal, and a second metal portion 31B that is a portion formed of the second metal.

[0043] When the conductive layer 30 is constructed only from the metal layer 31, the above-mentioned two types of metals (first metal, second metal) suitable for the conductive layer 30 can be appropriately combined and arranged so that the first metal portion 31A surrounds the second metal portion 31B, thereby making it possible to utilize the advantages of both (high durability, high conductivity) while compensating for the disadvantages of both (low durability, low conductivity) (see Figure 8).

[0044] The conductive layer 30 may have the form shown in FIG. 2, or may have the forms shown in FIGS. 5 to 8 as modified examples.

[0045] As shown in Fig. 5, the conductive layer 30 may have a laminated structure in which a conductive layer 30 made of a second metal portion 31B is formed on an insulating substrate 10, and a transparent electrode layer 20 is formed on the conductive layer 30. In the embodiment shown in Fig. 5, the conductive layer 30 is formed of the second metal portion 31B, which has poor durability, and therefore the exposed portion of the outermost surface of the conductive layer 30 is covered with a current collecting portion 40 made of a first metal, which has excellent durability, and is therefore not exposed to the outside. In the embodiment shown in Fig. 5, since no openings 33 are formed in the conductive layer 30 made of only metal, it is preferable that the thickness of the conductive layer 30 is 5 nm or less from the viewpoint of transparency.

[0046] As shown in Fig. 6, the conductive layer 30 can have a laminated structure in which a conductive layer 30 made of a metal oxide layer 32 made of a metal oxide is formed on an insulating substrate 10, and a transparent electrode layer 20 is formed on the conductive layer 30. In the embodiment shown in Fig. 6, the conductive layer 30 is formed of a metal oxide having poor durability, but the exposed portion located on the outermost surface of the conductive layer 30 is covered with a current collecting part 40 made of a first metal having excellent durability, and therefore is not exposed to the outside. Therefore, the conductive layer 30 made of the metal oxide layer 32 can be made of a transparent conductive material having low durability, such as ITO.

[0047] As shown in FIG. 7, the conductive layer 30 can have a laminated structure in which a two-layer conductive layer 30 is formed on an insulating substrate 10, with a second metal portion 31B having an opening 33 as a metal layer 31 as a lower layer and a metal oxide layer 32 as an upper layer, and a transparent electrode layer 20 is formed on the conductive layer 30. The current collector 40 is made of a first metal and is formed so as to cover the outer peripheral surface of the conductive layer 30. In the embodiment shown in FIG. 7, the lower surface of the conductive layer 30 is entirely covered by the insulating substrate 10, and the exposed portion of the outermost surface is covered by the current collector 40 having excellent durability, and is therefore not exposed to the outside. Therefore, the conductive layer 30 can also have a metal oxide layer 32 formed of a transparent conductive material having low durability, such as ITO.

[0048] As shown in FIG. 8, the conductive layer 30 can have a laminated structure in which a two-layer conductive layer 30 is formed on an insulating substrate 10, with the second metal portion 31B as a lower layer and the first metal portion 31A as an upper layer, and a transparent electrode layer 20 is formed on the conductive layer 30. The conductive layer 30 is arranged so that the first metal portion 31A made of the first metal surrounds the second metal portion 31B made of the second metal. As a result, as shown in FIG. 8, the transparent electrode layer 20 enters the opening 33 during electrode formation, so that the second metal portion 31B is not exposed to the outside. Therefore, in the embodiment shown in FIG. 8, the second metal portion 31B can be prevented from being exposed, compensating for the durability, which is a drawback of the second metal, while utilizing the conductivity of the second metal portion 31B. In addition, in the embodiment shown in FIG. 8, the conductive layer 30 is made of metal and arranged to cover a part of the side portion 21 of the transparent electrode layer 20, so that the function of the current collecting portion 40 can be covered. Therefore, there is no need to provide a separate current collecting section 40, and the configuration can be simplified.

[0049] The thickness of the conductive layer 30 is preferably 5 nm to 100 nm from the viewpoints of transparency and conductivity, and is preferably thinner in consideration of transparency. The thickness of the conductive layer 30 can be appropriately set by the combination of the metal layer 31 and / or the metal oxide layer 32 while taking into consideration transparency, etc.

[0050] <Current collector> The current collecting part 40 is disposed so as to cover at least a portion of the side surface part 21 of the transparent electrode layer 20. As shown in Fig. 2, the current collecting part 40 is disposed on the edge part of the conductive layer 30, and can be disposed so as to cover a portion of the entire periphery of the side surface part 21 of the transparent electrode layer 20. The current collecting part 40 reduces the connection resistance between the transparent electrode layer 20 and an internal circuit (wristwatch, wearable device, etc.).

[0051] The constituent material of the current collecting part 40 is a metal material capable of electrically connecting with the transparent electrode layer 20 and the conductive layer 30. Specifically, the constituent material of the current collecting part 40 can suitably be the first metal (a metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd) used in the current collecting part 40. By forming the current collecting part 40 from the first metal, high durability can be obtained. Therefore, by forming the current collecting part 40 so as to cover at least a part of the side surface of the transparent electrode layer 20 and the outermost surface of the conductive layer 30, the durability of the transparent electrode 1 can be improved.

[0052] The transparent electrode layer 20, conductive layer 30, and current collecting portion 40 constituting the transparent electrode 1 can be formed by a method such as vacuum deposition, physical vapor deposition (PVD), chemical vapor deposition (CVD), spray pyrolysis (SPD), or an optimal method can be selected according to the material to be formed. In particular, the PVD method, which can form a dense thin film, is preferable.

[0053] As described above, the transparent electrode 1 according to the present embodiment is an electrode formed on the insulating substrate 10 and electrically connected to an object by contacting the object. The transparent electrode 1 is made of SnO 2 and a conductive layer 30 formed of a metal layer 31 and / or a metal oxide layer 32 having electrical conductivity, are laminated in this order from the outermost surface side, and at least a portion of a side portion 21 of the transparent electrode layer 20 is covered with a current collecting portion 40 that is electrically connected to the transparent electrode layer 20 and the conductive layer 30.

[0054] Furthermore, in the transparent electrode 1 according to this embodiment, when the metal layer 31 of the conductive layer 30 has a thickness exceeding 5 nm, it is preferable to form the metal layer 31 so that its projected area on the insulating substrate 10 in a planar view is 30% or less of the area of ​​the insulating substrate 10.

[0055] Moreover, in the transparent electrode 1 according to this embodiment, it is preferable that the metal layer 31 contains one or more elements selected from Ag, Al, Cr, Cu, Au, Pt, Ti, Mo, Nb, and Nd, and the transparent electrode layer 20 is formed containing one or more elements selected from In, Ga, Nb, Ta, W, Zn, Sn, Zr, Si, and F.

[0056] Furthermore, in the transparent electrode 1 of this embodiment, the metal layer 31 has a first metal portion 31A formed of a first metal selected from the group of Au, Pt, Ti, Mo, and Nd, and a second metal portion 31B formed of a second metal selected from the group of Ag, Al, Cr, Cu, and Nb, and it is preferable that the first metal portion 31A is positioned so as to prevent exposure of the second metal portion 31B.

[0057] Moreover, in the transparent electrode 1 according to this embodiment, the current collecting portion 40 is preferably formed of a first metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd, and is formed so as to cover at least a portion of the side portion 21 of the transparent electrode layer 20 and the outermost surface of the conductive layer 30.

[0058] In the transparent electrode 1 according to this embodiment, the transparent electrode layer 20 preferably has a film thickness of 50 nm or more and 200 nm or less.

[0059] Furthermore, the transparent electrode 1 described above can be provided in a measuring device such as a wearable device 100 having a measuring function including an optical measuring unit 120 and an electrical measuring unit 130.

[0060] With this configuration, the transparent electrode layer 20, which has both physical and chemical durability and transparency, can be arranged on the outermost surface, and by using it as an electrode for the electrical measurement unit 130, the electrode portion made of metal, which was conventionally optically opaque, can be made transparent. Therefore, in a wearable device 100 having a relatively small exterior area, it is possible to arrange the electrical measurement unit 130 and the optical measurement unit 120 in an overlapping manner. Therefore, the wearable device 100 equipped with the transparent electrode 1 has a higher degree of freedom in the measurement method while reducing design constraints, and more optical measurements are possible. In addition, by using the transparent electrode 1 of the present invention in the wearable device 100, etc., optical acquisition of biological information is possible over a larger area, and the measurement accuracy of biological information can be improved. Furthermore, when the electrode portion is composed only of a metal electrode as in the conventional product, the exterior is limited to a metallic opaque material from the viewpoint of design, but by using the transparent electrode 1 of the present invention, it is possible to apply a design to the lower layer of the electrode, and the design of the device can be improved. EXAMPLES

[0061] The effects of the present invention will be described using the following examples and comparative examples, although the technical scope of the present invention is not limited to the following examples.

[0062] [Evaluation test 1] Performance tests were carried out on each sample in the following examples and comparative examples.

[0063] <Sample Production> The samples of the examples (Examples 1 to 6) and the samples of the comparative examples (Comparative Examples 1 to 4) were produced according to the following steps.

[0064] Preparation of Sample of Example 1 The sample of Example 1 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass having a diameter of 26 mm, and then laminating a transparent electrode layer on top of that (shape shown in FIG. 8). The conductive layer and the transparent electrode layer were formed by sputtering. A DC magnetron sputtering device (manufactured by Showa Shinku Co., Ltd.) was used to form the conductive layer, and a sputtering device (manufactured by Toshima Manufacturing Co., Ltd.) was used to form the transparent electrode layer. The conditions for forming the conductive layer were a degree of vacuum of 10°C in the device, and a temperature of 10°C. -3 Ar gas was introduced at a pressure of 0.4 Pa or less, and the discharge power was DC 30 W. The deposition conditions for the transparent electrode layer were a vacuum degree of 10 in the device, -3 At a pressure of 0.4 Pa or less, Ar gas was introduced to set the pressure to 0.4 Pa, and the discharge power was RF 100 W. The substrate was heated to 100°C during film formation. The conductive layer was formed by laminating a first metal (Mo) with a thickness of 20 nm on a second metal (Al) with a thickness of 30 nm. The conductive layer was formed in a lattice shape by arranging multiple openings of 2 mm x 2 mm square in a matrix. The transparent electrode layer was made of SnO 2 A thin film containing the above as a main component was formed. Five types of samples of Example 1 were produced on the conductive layer with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm. The current collecting portion was also used as the conductive layer. The sample of Example 1 had the shape shown in FIG. 8.

[0065] Preparation of Sample of Example 2 The sample of Example 2 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed in the same manner as in Example 1. The conductive layer had no openings and was made of a second metal (Al) with a thickness of 3 nm. The transparent electrode layer was made of SnO 2 The samples of Example 2 were prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting portion was formed by covering the conductive layer with the first metal (Mo) so that the conductive layer was not exposed. The sample of Example 2 had the shape shown in FIG. 5.

[0066] Preparation of Sample of Example 3 The sample of Example 3 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed in the same manner as in Example 1. The conductive layer was made of a second metal (Al) with a film thickness of 30 nm. The conductive layer had a lattice shape with multiple openings of 2 mm x 2 mm squares arranged in a matrix. The transparent electrode layer was made of SnO 2 The samples of Example 3 were prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting portion was formed by covering the conductive layer with the first metal (Mo) so that the conductive layer was not exposed. The sample of Example 3 had the shape shown in FIG. 2.

[0067] Preparation of Sample of Example 4 The sample of Example 4 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed by sputtering in the same manner as in Example 1. The conductive layer had no openings and was made of a metal oxide (ITO) with a film thickness of 100 nm. The transparent electrode layer was made of SnO 2 The samples of Example 4 were prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting part was formed by covering the conductive layer with the first metal (Mo) so that the conductive layer was not exposed. The sample of Example 4 had the shape shown in FIG. 6.

[0068] Preparation of Sample of Example 5 The sample of Example 5 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed by the sputtering method as in Example 1. The conductive layer was formed by laminating a metal oxide (ITO) with a thickness of 100 nm on a second metal (Al) with a thickness of 30 nm. The layer made of the second metal had a lattice pattern with multiple openings of 2 mm x 2 mm squares arranged in a matrix. The transparent electrode layer was made of SnO 2The samples of Example 5 were prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting portion was formed by covering the conductive layer with the first metal (Mo) so that the conductive layer was not exposed. The sample of Example 5 had the shape shown in FIG. 7.

[0069] Preparation of Sample of Example 6 The sample of Example 6 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed by the sputtering method as in Example 1. The conductive layer was formed by laminating a first metal (Mo) with a thickness of 20 nm on a second metal (Al) with a thickness of 30 nm. The conductive layer was formed in a lattice shape by arranging multiple openings of 2 mm x 2 mm square in a matrix shape. The transparent electrode layer was made of SnO 2 The main component is SnO 2 A: 95 parts by mass, F: 5 parts by mass). Five types of samples of Example 6 were prepared with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm on the conductive layer. The current collecting portion was also used as the conductive layer. The sample of Example 6 has the same shape as Example 1, as shown in FIG. 8.

[0070] <Production of Sample of Comparative Example 1> The sample of Comparative Example 1 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass with a diameter of 26 mm, and then laminating a transparent electrode layer on top of that. The conductive layer and the transparent electrode layer were formed by the sputtering method similar to that of Example 1. The conductive layer was formed of a second metal (Al) with a film thickness of 30 nm. The layer formed of the second metal had a lattice shape with multiple openings of 2 mm x 2 mm arranged in a matrix. The transparent electrode layer was made of SnO 2 The sample of Example 5 was prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting portion was also used as the conductive layer. The sample of Comparative Example 1 was formed in a shape similar to that of Example 1, except that the first metal layer was not formed.

[0071] <Production of Sample of Comparative Example 2> The sample of Comparative Example 2 was prepared by laminating a conductive layer on an insulating substrate made of alkali-free glass having a diameter of 26 mm, and then laminating a transparent electrode layer on top of the conductive layer. The conductive layer and the transparent electrode layer were formed by the sputtering method in the same manner as in Example 1. The conductive layer was formed of a metal oxide (ITO) with a thickness of 100 nm. The transparent electrode layer was formed of SnO 2 The sample of Comparative Example 2 was prepared in five types, with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm, on the conductive layer. The current collecting portion was also used as the conductive layer. The sample of Comparative Example 2 was shaped such that the current collector of Example 4 was not formed.

[0072] <Production of Sample of Comparative Example 3> The sample of Comparative Example 3 was a 26 mm diameter insulating substrate made of alkali-free glass, on which no conductive layer was formed, and SnO 2 Only a transparent electrode layer consisting of the above was laminated. The transparent electrode layer was formed by the sputtering method in the same manner as in Example 1. Five types of samples of Comparative Example 3 were prepared with film thicknesses of 30 nm, 60 nm, 100 nm, 200 nm, and 300 nm on an insulating substrate. The sample of Comparative Example 3 has a shape in which the conductive layer of Comparative Example 2 is not formed.

[0073] <Production of Sample of Comparative Example 4> The sample of Comparative Example 4 was prepared by laminating only a conductive layer made of metal oxide (ITO) having a thickness of 100 nm on an insulating substrate made of alkali-free glass having a diameter of 26 mm, without forming a transparent electrode layer. The conductive layer was formed by a sputtering method similar to that of Example 1. The sample of Comparative Example 4 was formed in the same manner as Comparative Example 2, without forming a transparent electrode layer.

[0074] <Test Contents> Each sample of the examples and comparative examples prepared by the above-mentioned procedures was subjected to a physical durability test, a chemical durability test, a conductivity test, and a transparency test.

[0075] Physical durability test For the physical durability test, a φ6mm eraser was placed on the surface of the transparent electrode layer of each sample with a load of 1kg applied, and a reciprocating friction tester (product name: TYPE30S, manufactured by Shinto Scientific Co., Ltd.) was used to move the eraser 3,000 times at a distance of 15mm and a speed of 40 reciprocations / min. After the test, the electrodes were evaluated by visual inspection and by using a microscope to check for scratches on their exterior. The evaluation criteria were as follows: ○: No scratches by visual or microscopic observation △: No scratches when observed visually, scratches when observed under a microscope ×: Scratches observed visually and under a microscope.

[0076] Chemical durability test Chemical durability tests were performed using a solution adjusted to pH 4.6 (buffer solution pH 4.6 (C 8 H 5 KO 4 The transparent electrodes were placed in a 100% NaOH (manufactured by Tokyo Chemical Industry Co., Ltd.) solution so that some were immersed and some were not, and the electrodes were left for 48 hours, after which the appearance change before and after the test was observed. The evaluation criteria were as follows: 〇: Changes ×: No change.

[0077] Conductivity Test The electrical conductivity test was carried out by measuring the surface resistance (Ω / sq) at the centre of the sample using a surface resistance meter (product name: Loresta-GX MCP-T700, manufactured by Nitto Seiko Analytech Co., Ltd.) with four terminals. In addition, the resistance (Ω) between the centre of the sample and the current collector (approximately 15 mm) was measured using a resistance meter (product name: RM3548, manufactured by Hioki E.E.C. Co., Ltd.). The evaluation criteria were as follows: ·Surface resistance ○: Less than 200Ω / sq ×:200Ω / sq or more Center-to-current collector resistance ○: Less than 220Ω ×: 220Ω or more.

[0078] <Transparency test> The transparency test was carried out using an ultraviolet-visible spectrophotometer (product name: UV-1900, manufactured by Shimadzu Corporation) to calculate the average transmittance of each sample at wavelengths of 530 nm, 660 nm, and 940 nm. The evaluation criteria were as follows: 〇: Average transmittance 80% or more △: Average transmittance 70% or more and less than 80% ×: Average transmittance less than 70%.

[0079] <Result> Fig. 9 shows the specifications and the results of evaluation test 1 for each sample of Examples 1 to 3. Fig. 10 shows the specifications and the results of evaluation test 1 for each sample of Examples 4 to 6. Fig. 11 shows the specifications and the results of evaluation test 1 for each sample of Comparative Examples 1 to 4.

[0080] As shown in the tables of FIG. 9 or FIG. 10, the sample of Example 1 with a transparent electrode layer having a thickness of 100 nm, the samples of Example 2 with transparent electrode layers having thicknesses of 60 nm and 100 nm, the sample of Example 3 with a transparent electrode layer having a thickness of 100 nm, and the samples of Examples 4 and 5 with transparent electrode layers having thicknesses of 30 nm, 60 nm, and 100 nm were all evaluated as "good" for physical durability, chemical durability, conductivity, and transparency, and it was found that sufficient quality could be guaranteed as a product. Furthermore, from the results of Examples 1 to 6, it was found that "chemical durability of the exposed part of the conductive layer (current collector) can be obtained by coating the second metal of the conductive layer with the first metal", "transparency can be ensured by setting the film thickness of the transparent electrode layer to 50 nm or more and 200 nm or less", "transparency can be ensured regardless of the film thickness of the conductive layer by forming an opening in the conductive layer", "chemical durability can be obtained by forming the current collector with the highly durable first metal and coating it with the conductive layer", and "SnO 2 It was found that by adding a specific additive to the transparent electrode layer, which is mainly composed of , the crystal grains in the film do not grow large, and the physical durability does not decrease even when the film is made thick.

[0081] On the other hand, as shown in the table of FIG. 11, the results of chemical durability or conductivity of Comparative Example 1 to Comparative Example 4 were not good, and it was found that the product quality was not satisfactory. In addition, from the results of Comparative Example 1 to Comparative Example 4, it was found that "when the transparent electrode layer is made thinner, the transparency tends to improve, but the physical durability and conductivity decrease", "when the transparent electrode layer is made thicker, the conductivity tends to improve, but the transparency decreases", "when a conductive layer formed of a second metal is used as a current collector, the second metal with low durability is exposed, so chemical durability cannot be obtained", "when the film thickness of the transparent electrode layer is 60 nm or less due to the opening step of the conductive layer, the coverage of the conductive layer is insufficient and physical durability cannot be obtained", "when the film thickness of the transparent electrode layer is 200 nm or more, transparency decreases", "when a conductive layer (metal oxide) is used as a current collector, chemical durability cannot be obtained because the metal oxide is exposed", "with only the transparent electrode layer, durability can be obtained but conductivity is difficult to ensure", and "with only the conductive layer, it is difficult to ensure chemical durability".

[0082] [Evaluation test 2] Performance tests were carried out on each sample in the following examples and comparative examples.

[0083] <Sample Production> The transparent electrode layers in both Examples A and B were formed by sputtering.

[0084] The transparent electrode layer of Comparative Example C was formed by a coating pyrolysis method.

[0085] The surface roughness Ra and maximum height roughness Rz of each sample were analyzed using a scanning probe microscope (SPM) (product name: SPM-9700HT, manufactured by Shimadzu Corporation). The average particle size was measured using a SEM device (product name: Dual Beam FIB Helios 5 UC, manufactured by Thermo Scientific). The film density was measured by X-ray reflectometry (XRR) using a fully automatic sample horizontal multipurpose X-ray diffraction device (product name: SmartLab, manufactured by Rigaku Corporation).

[0086] <Test Contents> In evaluation test 2, similar to the physical durability test in evaluation test 1, a φ6 mm eraser was placed on the surface of the transparent electrode layer of each sample with a load of 1 kg applied, and the eraser was moved back and forth 3,000 times at a moving distance of 15 mm and a moving speed of 40 reciprocations / min. After the test, the electrodes were evaluated by visual inspection and by using a microscope to check for scratches on their exterior. The evaluation criteria were as follows: ○: No scratches by visual or microscopic observation ×: Scratches observed visually and under a microscope.

[0087] <Result> FIG. 12 shows the results of evaluation test 2. It was found that both Example A and Example B had good durability. In contrast, Comparative Example C had poor durability results and was found to be unable to satisfy product quality. From the standpoint of durability, it was found that the transparent electrode layer of the transparent electrode had a surface roughness Ra of 3.3 nm or less, a maximum height roughness Rz of 33 nm or less, and a film density of 6.8 g / cm. -3 It was found that by making the above adjustments, a transparent electrode with excellent durability could be obtained. [Explanation of symbols]

[0088] 1 transparent electrode, 10 insulating substrate, 20 transparent electrode layer, 21 side part, 30 conductive layer, 31 metal layer, 31A 1st metal part, 31B 2nd metal part, 32 metal oxide layer, 40 current collector, 100 A wearable device that functions as a measuring device; 110 Device body, 120 Optical measurement section, 130 Electrical measuring unit, 140 Display section, 150 control section, 160 Power supply section.

Claims

1. A transparent electrode formed on an insulating substrate and electrically connected to an object by contacting the object, The transparent electrode is made of SnO 2 and a conductive layer formed of a metal layer and / or a metal oxide layer having electrical conductivity, laminated in this order from the outermost surface side, A transparent electrode, wherein at least a portion of a side surface of the transparent electrode layer is covered with a current collecting portion electrically connected to the transparent electrode layer and the conductive layer.

2. The transparent electrode according to claim 1 , wherein the metal layer of the conductive layer is formed so that, when the metal layer has a thickness exceeding 5 nm, a projected area on the insulating substrate in a plan view is 30% or less of an area of ​​the insulating substrate.

3. The metal layer contains one or more elements selected from Ag, Al, Cr, Cu, Au, Pt, Ti, Mo, Nb, and Nd, 2. The transparent electrode according to claim 1, wherein the transparent electrode layer contains one or more elements selected from the group consisting of In, Ga, Nb, Ta, W, Zn, Sn, Zr, Si, and F.

4. The metal layer has a first metal portion formed of a first metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd, and a second metal portion formed of a second metal selected from the group consisting of Ag, Al, Cr, Cu, and Nb, The transparent electrode according to claim 1 , wherein the first metal portion is disposed so as to prevent exposure of the second metal portion.

5. 2. The transparent electrode according to claim 1, wherein the current collecting portion is formed of a first metal selected from the group consisting of Au, Pt, Ti, Mo, and Nd, and is formed so as to cover at least a portion of a side portion of the transparent electrode layer and an outermost surface of the conductive layer.

6. The transparent electrode according to claim 1 , wherein the transparent electrode layer has a film thickness of 50 nm or more and 200 nm or less.

7. A measuring device comprising the transparent electrode according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Display unit having decorative effect of portable instrument, such as watch

    JP2007121303A